Trisomy 11 as an Additional Chromosome Alteration in a Child with Acute Promyelocytic Leukemia with Poor Prognosis - Elenice Ferreira Bastos; Lidiane Alice Silva; Marcelo Coelho Ramos; Glicínia Pimenta; Paulo Ivo Cortez; Stella Beatriz Gonçalves de Lucena; Teresa de Souza Fernandez (Case Reports in Genetics)
The prognostic significance of the additional abnormalities to the t(15; 17) remains controversial. We report a case of promyelocytic leukemia (APL) in a ten-year-old boy. Classical and molecular cytogenetic (FISH) studies of a bone marrow sample obtained at diagnosis revealed the presence of trisomy of chromosome 11 as an additional chromosomal abnormality to the t(15; 17). The presence of the translocation t(15; 17), the cytogenetic marker of APL, is usually associated with good response to treatment with ATRA. In this case, although the patient had risk factors associated with good prognosis, he evolved and died quickly. So it seems that the presence of the trisomy 11 may be associated with disease progression and the poor outcome. To our knowledge, this is the first reported case of t(15; 17) associated with trisomy of chromosome 11 in a child with APL.